Proliferative Verrucous Leukoplakia of the Gingiva: An Early Lesion Refractory to Surgical Excision - Dhanushka Leuke Bandara; Primali Rukmal Jayasooriya; Ruwan Duminda Jayasinghe (Case Reports in Dentistry)
This report describes a case of proliferative verrucous leukoplakia (PVL) of the gingiva with no discernible aetiology, which presented in a 36-year-old female. The initial nonscrapable gingival lesion was treated with CO2 laser ablation, and the histopathological evaluation was carried out. The presence of koilocytic cells in the superficial epithelium led to immunohistochemical investigations with p16 antibody, which showed strong nuclear positivity and slight cytoplasmic positivity in >50% of the cells with >25% confluency. However, it was not possible to confirm the presence of HPV infection with further investigations due to logistic reasons. The lesion recurred twice within a short time despite the surgical resection following the first recurrence. Thus, this paper presents a case of proliferative verrucous leukoplakia, which demonstrated a significant resistance to routine treatment protocols recommended in the management of such lesions.